High-performance liquid chromatographic studies of the acid degradation, pharmacokinetics and comparative bioavailability of erythromycin - Glew, Fiona (Rhodes University, Faculty of Pharmacy, Pharmacy, 1989)
Erythromycin is a macrolide antibiotic with a spectrum similar to penicillin and is used mainly in the treatment of infections caused by gram-positive organisms. Since its discovery in 1952, erythromycin has achieved wide-spread clinical use. Susceptibility of erythromycin base to inactivation by acid results in decreased availability following exposure to acidic gastric fluids. Formulation of acid resistant dosage forms and the preparation of acid stable chemical derivatives have been attempted to improve absorption and subsequent clinical efficacy . Two of the most commonly used erythromycin derivatives are the stearic acid salt (erythromycin stearate) and the lauryl sulphate salt of the propionyl ester (erythromycin estolate). Although it has been known for many years that erythromycin is susceptible to acid degradation, very few reports on the stability of erythromycin in aqueous solutions appear in the literature. In this study, a high-performance liquid chromatographic system using electrochemical detection was employed for a kinetic study of erythromycin degradation. The effect of varying acid pH on the degradation rate of both erythromycin base and erythromycin stearate, and the effect on the hydrolysis rate of erythromycin estolate is presented. In addition, the effect of temperature on erythromycin degradation was also investigated. Until recently, the majority of pharmacokinetic and bioavailability studies have utilized relatively non-specific microbiological assay procedures. However, in this study a solid phase extraction, followed by the use of a high-performance liquid chromatographic system using electrochemical coulometric detection was employed for the determination of erythromycin in biological fluids. Human volunteers each received enteric coated erythromycin base pellets in capsule dosage form and also film coated erythromycin stearate tablets on separate occasions. Results from the clinical trials revealed the enteric coated erythromycin base pellets had a greater bioavailability than the film coated erythromycin stearate tablets. Computer fitting of data revealed no intra-volunteer variability in elimination rate constants, suggesting differences in serum levels following administration of both dosage forms are due to variation in absorption. Results from the clinical trials were also compared with those obtained from a further trial, during which the same volunteers received erythromycin estolate
Keywords: High performance liquid chromatography; Erythromycin -- Analysis; Erythromycin -- Pharmacokinetics; Erythromycin -- Bioavailability